THE EFFECT OF ERYTHROPOIETIN DOSE PHASE OF CORRECTION AS DRUG-RELATED PROBLEMS TO TARGET LEVEL OF HEMOGLOBIN IN REGULAR HEMODIALYSIS PATIENTS - Luthvia, Luthvia; Harahap, Urip; Nasution, Syafrizal (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Objectives: This research aims to know the effect of drug-related problems (DRPs)-related doses against the target hemoglobin levels in hemodialysis (HD) patients in the regular phase of the correction given the therapy of erythropoietin on H. Adam Malik Medan. Methods: This research was by the cross-sectional, prospective method, using DRP - Registration Form V7.0 (PCNE) against 50 patients. The data were analyzed statistically using Chi-square test, paired t-test sample, and independent t-test, SPSS version 17. Results: The target hemoglobin not reaching 30 patients (60%), the level of hemoglobin target exceeded target 1 of the patients (2%). Based on the results of the test t, the value of p=0.038<0.05, then there is a difference in the level of hemoglobin after providing significant erythropoietin therapy between doses and less excess. Test the level of hemoglobin of erythropoietin therapy before and after using a test sample. Paired t-test based on the results, obtained significant value is 0.05, then 0.015< increased hemoglobin level after statistics are given significant therapy of erythropoietin. Conclusion: The results of this study indicate that there is an effect of DRPs related to excessive dosage; less dose to target hemoglobin level with significant value, so DRPs-associated dose affect the target hemoglobin level. Â 